(untitled) (Eurasian Research Bulletin, 2022)
This multistep technique engages students in authentic discussion at several levels and uses a variety of language skills and functions. Because of the technique’s simplicity, it could be used with almost any age and level of student, except very young learners and beginners. To start off, students have to be familiar enough with the topic to be able to develop their questions; that may require them to read about or do research on the topic and to discuss it with classmates. Or, students can develop questions about a topic the class has recently studied